Being Short, Sweet, and Sour: Congruent Visuo-Olfactory Stimulation Enhances Illusory Embodiment. (June 2020) - Roel Lesur, Marte; Aicher, Helena; Delplanque, Sylvain; Lenggenhager, Bigna
Bodily self-identification has shown to be easily altered through spatiotemporally congruent multimodal signals. While such manipulations are mostly studied through visuo-tactile or visuo-motor stimulation, here we investigated whether congruent visuo-olfactory cues might enhance illusory self-identification with an arbitrary object. Using virtual reality, healthy individuals saw a grapefruit from its supposed first-person perspective that was touched in synchrony with their own body. The touch attempted to replicate what was seen as softly squeezing the grapefruit. Crucially, when we additionally presented the smell of a grapefruit in synchrony with the squeezing, they self-identified stronger with the fruit than when they smelled strawberry.